Problematika Hakim dalam Menghadapi Antinomi - Ach. Tahir (UIN Sunan Kalijaga Yogyakarta, 2012)
In deciding some cases, judges might get various antinomies. Antinomy is a contradiction between legal interests based on justice of each disputed party. The made decision must proportionally contain three principles: certainty, usefulness, and justice. If they obtain the contradiction between the principle of justice and legal certainty, they should prioritize the former. If they get the contradiction between an old statute and a new statute not abrogating the old one, they must enact the new one (lex posteriori derogat legi priori). If they find the contradiction between a superior statute and an inferior statute, they must use the superior one (lex superior derogat legi inferiori). If they get the contradiction between a statute and an court decision (Jurisprudence), they must use the latter (res judicata pro veritate habetur). If they get the contradiction between a statute and a custom law, they must prioritize the latter.